Injury-induced KIF4A neural expression and its role in Schwann cell proliferation suggest a dual function for this kinesin in neural regeneration - Patrícia D. Correia; Bárbara M. de Sousa; Jesús Chato-Astrain; Joana Paes de Faria; Veronica Estrada; João B. Relvas; Hans W. Müller; Víctor Carriel; Frank Bosse; Sandra I. Vieira (Neural Regeneration Research)
Contrary to the adult central nervous system, the peripheral nervous system has an intrinsic ability to regenerate that relies on the expression of regeneration-associated genes, such as some kinesin family members. Kinesins contribute to nerve regeneration through the transport of specific cargo, such as proteins and membrane components, from the cell body towards the axon periphery. We show here that KIF4A, associated with neurodevelopmental disorders and previously believed to be only expressed during development, is also expressed in the adult vertebrate nervous system and up-regulated in injured peripheral nervous system cells. KIF4A is detected both in the cell bodies and regrowing axons of injured neurons, consistent with its function as an axonal transporter of cargoes such as β1-integrin and L1CAM. Our study further demonstrates that KIF4A levels are greatly increased in Schwann cells from injured distal nerve stumps, particularly at a time when they are reprogrammed into an essential proliferative repair phenotype. Moreover, Kif4a mRNA levels were approximately ~6-fold higher in proliferative cultured Schwann cells compared with non-proliferative ones. A hypothesized function for Kif4a in Schwann cell proliferation was further confirmed by Kif4a knockdown, as this significantly reduced Schwann cell proliferation in vitro. Our findings show that KIF4A is expressed in adult vertebrate nervous systems and is up-regulated following peripheral injury. The timing of KIF4A up-regulation, its location during regeneration, and its proliferative role, all suggest a dual role for this protein in neuroregeneration that is worth exploring in the future.